2017
DOI: 10.4236/ojrd.2017.73010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ColdZyme Mouth Spray for the Protection against Common Cold in Elite Athletes to Reduce Unwanted Absence from Training and Competition

Abstract: This study evaluated the protective effect of ColdZyme on common cold infections in elite athletes from three different sports (biathlon, ice-hockey and handball), and assessed the level of reduction in corresponding sick days. The biathlon team (n = 11) and the ice-hockey team (n = 29) significantly reduced the average number of sick days by 51% respectively 67% compared to historical data. No historical data on sick days was available for the handball team but 76% of those who experiences a cold during the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…These results support previous findings from a double-blind, placebo-controlled study, where subjects treated with ColdZyme displayed significantly decreased viral load and fewer days with common cold symptoms [10]. In the previously referred study [18] athletes who had less than 2 sick days during the preceding months did seem to be less prone to catch a cold during the study period. However, those individuals that reported more than two sick days during the three months preceding the actual survey, seemed to benefit more from using ColdZyme [18].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These results support previous findings from a double-blind, placebo-controlled study, where subjects treated with ColdZyme displayed significantly decreased viral load and fewer days with common cold symptoms [10]. In the previously referred study [18] athletes who had less than 2 sick days during the preceding months did seem to be less prone to catch a cold during the study period. However, those individuals that reported more than two sick days during the three months preceding the actual survey, seemed to benefit more from using ColdZyme [18].…”
Section: Discussionsupporting
confidence: 81%
“…ColdZyme use reduced the number of sick days due to common cold, with a corresponding reduction in absence from training by >50% among the study participants [18]. These results support previous findings from a double-blind, placebo-controlled study, where subjects treated with ColdZyme displayed significantly decreased viral load and fewer days with common cold symptoms [10].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, no randomised controlled trials have examined whether such products can reduce URTI/URS incidence or duration in athletic populations. One recent study (Clarsund, 2017) did examine ColdZyme in athletes, but it lacked a control group and made comparisons with retrospective historical data from athlete's own training diaries, which has obvious limitations for establishing efficacy. The aims of this study were, therefore, to assess the efficacy of ColdZyme on URTI incidence, symptom ratings, and missed (or reduced) training in competitive endurance athletes under free‐living conditions, in a prospective randomised controlled trial.…”
Section: Introductionmentioning
confidence: 99%
“…The other study reports on an open survey in 113 caregivers active in elderly care: based on the analysis of the e-data responses by the participants, it could be deduced that 51/71 users (72%) contracted a cold, in comparison to 15/40 non-users, as reported in the discussion (37%) [ 55 ]. Vice versa, two more open studies in athletes revealed similarly low protection rates with Viruprotect (38–39%) [ 58 , 59 ]. Thus, based on these trials, the calculated protection among users varied between 9%-39% versus 31%-63% among non-users.…”
Section: Resultsmentioning
confidence: 99%